Spectroscopic ellipsometric determination of optical properties of V-Al co-doped ZnO films by rf magnetron sputtering - Sayari, A.; El Mir, L.; Al-Heniti, S.; Shalaan, E.; Yaghmour, S. J.; Al-Thabaiti, S. A.; Yakuphanoğlu, Fahrettin (Springer, 2013)
Zn0.9-xV0.1AlxO aerogel nanopowders were prepared in thin film form on glass substrates using a rf magnetron sputtering system. The films were characterized by Scanning electron microscopy (SEM) and X-ray diffraction technique (XRD). The XRD results indicate that all the films have c-axis preferred orientation due to self-texturing mechanism. The ellipsometric spectra of the films were recorded in the photon energy range of 1 eV-5 eV. The SE spectra were analyzed with an appropriate model to accurately determine the thickness and optical constants of the ZnO:(V,Al) thin films. The profiles of refractive index and extinction coefficient with photon energy were extracted. The refractive index of the ZnO:(V,Al) film is decreased from 2.14 to 2.07 with increasing Al concentration and then is increased to 2.19 for x = 0.04. A maximum band gap energy of similar to 3.57 eV was obtained for x = 0.02. The optical band gaps of the films were found to vary from 3.57 eV to 3.41 eV, with Al content. It is evaluated that the optical constants of the ZnO:(V,Al) films can be controlled by Al content.
Keywords: ZnO; Aerogel; Thin film; Spectroscopic ellipsometry; Optical constant